The Pathway Less Traveled: Engineering Biosynthesis of Nonstandard Functional Groups. Issue 5 (May 2020) - Sulzbach, Morgan; Kunjapur, Aditya M.
Abstract : The field of metabolic engineering has achieved biochemical routes for conversion of renewable inputs to structurally diverse chemicals, but these products contain a limited number of chemical functional groups. In this review, we provide an overview of the progression of uncommon or 'nonstandard' functional groups from the elucidation of their biosynthetic machinery to the pathway optimization framework of metabolic engineering. We highlight exemplary efforts from primarily the last 5 years for biosynthesis of aldehyde, ester, terminal alkyne, terminal alkene, fluoro, epoxide, nitro, nitroso, nitrile, and hydrazine functional groups. These representative nonstandard functional groups vary in development stage and showcase the pipeline of chemical diversity that could soon appear within customized, biologically produced molecules. Highlights: Nonstandard functional groups that are derived from natural products face many hurdles prior to mainstream integration into engineered products, including pathway discovery, heterologous expression, and product stability. Metabolic engineers have achieved control over formerly uncommon groups such as aldehydes, esters, terminal alkynes, terminal alkenes, and fluorinated chemicals, by addressing the challenges above, as well as by increasing protein activity and expanding product range. Recently discovered pathways for formation of nonstandard groups such as nitro, nitrile, epoxide, nitroso, and hydrazine could benefit from more investigation of activity towards nonnative substrates for eventual integration into valuable products in agriculture, materials, pharmaceuticals, and more.